The use of stevia leaves in the production of some baked products - Farhan, Magda Abdel Jalil; Abdel Latif, Buthaina Mohamed (Journal of agricultural, environmental and veterinary sciences, 2018)
The aim of study is to use the powder of dried stevia leaves and thepurified stevia as partial substitution of sucrose to produce cakes، and cookies. The obtained data indicated that the chemical composition of dried stevia leaves had higher contents of dietary fiber 66.83%، total sugars 17.24%. Also it contained higher contents of potassium، calcium and Sodium and contained lower contents of iron، magnesium، Zinc and copper. The dried stevia leaves contained 13.76% of stevioside and 2.23% of Rebaudioside A as detected by H.P.L.C، while the purified stevia contained 87.21% of stevioside and 5.94% of Rebaudioside A. The results also indicated that dried stevia leaves had bitter taste and had the relative sweetness of 110 times sweeter than sucrose، while the purified stevia had relative sweetness 190 times sweeter than sucrose. Also، the color of crust and crumb of cake made using different levels of purified stevia had no significant difference. While the color of crust and crumb of cake made using different levels of dried stevia leaves was darker compared with control cake. The moisture contents of cake made using the previous substitution decreased with increasing، the storage periods. Compressibility as indicated by penetrometer decreased by increasing the storage period، while these decreased in moisture of compressibility was lower compared with control sample. Over all acceptability of Cake made using 25% of dried stevia leaves، or cake made using 50% of purified stevia with the other substitution and control samples of cake.